Endogenous time preference, investment and development traps - Pertti Haaparanta; Mikko Puhakka (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
We introduce endogenous time preference via investment in patience (farsightedness) in an overlapping generations growth model to study development traps.There is no investment in patience, if the economy is very poor, while if it is wealthy enough there is always such investment.We explore the conditions for the existence of the development trap, and study in detail a robust example of an economy with traps.It does not exist, if the economy's total factor productivity is large enough.Our results illustrate the complementarity between physical investment and investment in farsightedness.Our model may also explain why economic growth is affected by initial conditions.In addition we show that increased international capital mobility does not necessarily help economies to escape from development traps.
URN:NBN:fi:bof-201408072016
Keywords: I30; O11; O16; 330; development trap; overlapping generations